2018
DOI: 10.1111/cei.13156
|View full text |Cite
|
Sign up to set email alerts
|

Circulating serum miR-223-3p and miR-16-5p as possible biomarkers of early rheumatoid arthritis

Abstract: Small non-coding RNAs have emerged as possible biomarkers for various diseases including autoimmune diseases. A number of studies have demonstrated that the expression of specific microRNAs (miRNAs) is dysregulated in rheumatoid arthritis (RA). So far, all studies on miRNAs in RA patients have been performed using either microarray or reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analyses. Compared to RT-qPCR and microarray analyses, next-generation sequencing (NGS) allows the genome-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 44 publications
1
51
1
Order By: Relevance
“…89 Mechanism studies have found that endonuclease Dicer and angiogenin temporarily regulate the biogenesis of tRF5-AlaCGC, and this tRF could enhance IL-8 expression by activating p65. 91 Intriguingly, although the levels of tRFs in early RA were approximately the same as in healthy subjects, the proportion of reads mapped to tRNA in early RA was higher, which deserves our attention. 90 Dunaeva et al demonstrated that miR-223-3p and miR-16-5p were dysregulated in rheumatoid arthritis (RA) and could be used as biomarkers for this disease.…”
Section: Trna Derivatives and Immune Responsesmentioning
confidence: 89%
See 1 more Smart Citation
“…89 Mechanism studies have found that endonuclease Dicer and angiogenin temporarily regulate the biogenesis of tRF5-AlaCGC, and this tRF could enhance IL-8 expression by activating p65. 91 Intriguingly, although the levels of tRFs in early RA were approximately the same as in healthy subjects, the proportion of reads mapped to tRNA in early RA was higher, which deserves our attention. 90 Dunaeva et al demonstrated that miR-223-3p and miR-16-5p were dysregulated in rheumatoid arthritis (RA) and could be used as biomarkers for this disease.…”
Section: Trna Derivatives and Immune Responsesmentioning
confidence: 89%
“…90 Dunaeva et al demonstrated that miR-223-3p and miR-16-5p were dysregulated in rheumatoid arthritis (RA) and could be used as biomarkers for this disease. 91 Intriguingly, although the levels of tRFs in early RA were approximately the same as in healthy subjects, the proportion of reads mapped to tRNA in early RA was higher, which deserves our attention.…”
Section: Trna Derivatives and Immune Responsesmentioning
confidence: 89%
“…miRNA 26 are systemically elevated in RA, while hsa‐mir‐26b‐5p, in particular is implicated in autoimmune psoriasis . Hsa‐mir‐16‐5p regulates immune, apoptosis and epithelial barrier functions, and is an emerging biomarker of early disease and therapeutic response in RA . It is also upregulated in periodontitis .…”
Section: Discussionmentioning
confidence: 99%
“…73 Hsa-mir-16-5p regulates immune, apoptosis and epithelial barrier functions, and is an emerging biomarker of early disease and therapeutic response in RA. 74,75 It is also upregulated in periodontitis. 76 HMOX1 and SP1, the hub genes nodes in the gene-miRNA network both are involved in bone and immune regulation.…”
Section: Micrornasmentioning
confidence: 99%
“…12 Previous studies illustrated that miR-16 were increased in the sera of established RA patients in comparison with early RA. 13,14 MiR-16 were shown to be overexpressed at the systemic level: in both the periphery and RA joints. 15 Upregulation of miR-16 is demonstrated to be involved in Th17/Treg cell imbalance in patients with RA.…”
Section: Introductionmentioning
confidence: 99%